Implementasi Qr Code Menggunakan Google Application Programming Interface (API) Dalam Membangun Sistem Informasi Warehouse Dengan Metode Extreme Programing Berbasis Web (Studi Kasus : Pt Bell Flavors & Fragrances Indonesia) - Juli Bima Ardika; Niki Ratama (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2022)
The warehouse information system is a system that functions to control the course of transactions that occur in the warehouse. QR Code implementation is the application of a QR code that is created using the Google API and functions to view details of goods transactions and inventory. In the process of transactions carried out manually at PT. Bell Flavors & Fragrances Indonesia, which is a private company in the field of distributors of chemicals and products produced, namely, Flavors, Fragrances, Botanicals, Ingredient Specialties by inputting data into Microsoft Excel which was previously written manually on HVS paper takes a lot of time and causes errors on recording. The extreme programming method is used to solve problems that occur with the planning, design, coding, and testing stages. The information system built using the PHP programming language using Unified Modeling Language (UML) object-oriented analysis such as Use Case Diagrams, Sequence Diagrams, Activity Diagrams and Class Diagrams and using Black Box testing, White Box testing and questionnaire testing.